Republic of Serbia : Staff Report for the 2006 Article IV Consultation and Post-Program Monitoring Discussions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Failed corporate structures lie at the heart of Serbia's economic difficulties. But the government emphasized instead the need for public investment and labor tax cuts. Capital inflows pose additional challenges. External concerns leave little room to fiscal maneuver. This puts the focus on public expenditure reform. Recent changes in monetary arrangements are appropriate. These steps would best be taken further-toward inflation targeting. However, the envisaged fiscal relaxation calls much of this into question. Serbia has made significant progress in recent years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet